OPERATIONAL AND STRATEGIC CONTROLLING IN HOLDINGS - N. A. Kazakova; Ye. A. Khlevnaya; L. K. Tsvetkova (Финансы: теория и практика)
The globalization of the economy, innovations in science and engineering, rapid development of information technologies have resulted in the increased competition and higher instability of the environment.The management today is increasingly challenged by the problem of control caused by a number of factors: economic crises, the increased volume and diversity of its own activities, the dynamics and complexity of the corporate environment as well as the severe market competition. The problem of effective control in holding companies is coming to the fore. The paper compares different approaches to the management of an enterprise and reveals advantages and disadvantages of each.As a result of the analysis, a classification of practical tools and methods for strategic and operational controlling has been proposed to ensure efficient and sound management of company flows in both the short and long term when setting targets and developing ways to achieve them.